Strategi pengembangan inovasi produk lokal makanan tiwul dalam peningkatan daya tarik wisata Kabupaten Gunung Kidul - Nugroho, Dwi Yoso; Triyono, Joko (Journal of Management and Digital Business, 2024)
This research aims to identify effective development strategies for attracting tourists to Gunungkidul Regency, especially regarding Nasi Tiwul culinary tourism. This research is library research. Research findings show that Nasi Tiwul has a high urgency in increasing tourism attractiveness in Gunungkidul Regency based on its cultural value, ability to diversify culinary delights, local economic benefits, environmental sustainability, tourist attractiveness, and potential for increasing employment opportunities. With the proper strategic steps, Nasi Tiwul can become one of the culinary icons of Gunungkidul Regency, known locally and internationally. However, there are several inhibiting factors in developing Nasi Tiwul as part of local tourism namely Nasi Tiwul is considered old school or ancient food, tourists, especially young people, do not really like Nasi Tiwul, there is a lack of innovation in serving Nasi Tiwul, and unstable cassava production.